(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article provides a comprehensive analysis of the legal and ethical foundations of backbiting (ghibah) and slander (buhtan) on digital platforms. Drawing on official documents of the Muslim Board of Uzbekistan and the Cabinet of Ministers of the Republic of Uzbekistan, the article broadly addresses the application of ethical and legal norms in social media, the adverse social impact of ghibah and buhtan, and the responsibility of both society and the individual in preventing them. The study scientifically substantiates the harmony between Islamic values and national-legal foundations in the contemporary digital environment.